Hubungan Tingkat Literasi Gizi pada Status Gizi Siswa SMA (Studi pada Siswa/i SMAN 1 Kota Tangerang) - Dicky Andhyka Priambudi; Farapti Farapti (Media Gizi Kesmas, 2023)
Background: Nutritional literacy is a measure of an individual's ability to obtain, process, and understand information related to nutrition to be used as a basis for decision-making related to nutrition. Individual decisions related to nutrition play a major role in determining eating patterns and physical activity. Objectives: This study aimed to analyze the relationship between nutritional literacy level on the nutritional status of students at SMAN 1 Kota Tangerang. Methods: This was an observational study with a cross-sectional research design. The research location was conducted at SMAN 1 Kota Tangerang with a sample size of 168 people selected randomly using a purposive random sampling technique. Research data were collected by filling out a Google Forms questionnaire. Data were analyzed by the chi-square test. Results: The results showed that there was a relationship between mother's education level (p=0,031); pocket money (p=0,037); and gender (p=0,027) with nutritional status of students. Meanwhile, nutritional literacy which was divided into functional, interactive, and critical domains showed no relationship with nutritional status (p=0,054; p=0,687; and p=0,769). Conclusions: There was no direct relationship between nutritional literacy with the nutritional status of SMAN 1 Tangerang students. Strengthening nutrition education through the curriculum and collaboration of various parties is needed to achieve a better level of nutritional literacy.